The Influence of Dynamic Passing and Concentration on Increasing the Football Passing Ability of Students - Al Qadri Ilmi Sukisman Putra; Wahyuddin; Saleh, Muh. Sahib; Juhanis; Hudain, Muh. Adnan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The study's background is based on the fact that no previous study has examined the football passing skills of Smanko students in South Sulawesi. This research aims to examine the influence of moving passing and concentration training on improving the football passing skills of Smanko students in Sulsel. This study utilized an experimental approach, employing a one-group pretest-posttest design. The population consisted of Smanko Sulsel students, who were still actively participating in routine training. We used a sample of 24 athletes. The results of the study are: there is an influence of moving passing training in increasing football passing skills of Smanko students in Sulsel with an average score of 83.00 with a sig value of 0.000 (P<0.05), and there is an influence of concentration in increasing football passing skills of Smanko students in Sulsel, obtaining an average score of - mean 79.17 with a sig value of 0.000 (P<0.05). Therefore, we can conclude that moving passing and concentration training significantly enhance the football passing skills of Smanko students in Sulsel.